Computer Assisted Assessment of Thyroid Function - Law, Alan G. (1980)
With the use of a portable, stand-alone micro computer system at the time of initial interview, the thyroid test strategy for a patient can be produced automatically, along with the printout of the questionnaire information. The later phase of using the thyroid test results for preliminary assessment of glandular performance can also be produced by the micro computer -- effectiveness of the scheme is discussed for a number of test cases.